Dose-Response Transcranial Electrical Stimulation Study Design: A Well-Controlled Adaptive Seamless Bayesian Method to Illuminate Negative Valence Role in Tinnitus Perception - Ghodratitoostani, Iman; Gonzatto, Oilson A.; Vaziri, Zahra; Delbem, Alexandre C. B.; Makkiabadi, Bahador; Datta, Abhishek; Thomas, Chris; Hyppolito, Miguel A.; Santos, Antonio C. D.; Louzada, Francisco; Leite, João Pereira (Frontiers in Human Neuroscience, 2022)
Background The use of transcranial Electrical Stimulation (tES) in the modulation of cognitive brain functions to improve neuropsychiatric conditions has extensively increased over the decades. However, the techniques have raised new challenges associated with study design, stimulation protocol, functional specificity, and dose-response relationship. This study addresses these challenges that were prototyped methodology to identify the role of negative valence in tinnitus perception through a dose-response relationship study of High Definition Transcranial Direct Current Stimulation (HD-tDCS). In light of the neurofunctional testable framework predictions and tES application, hypotheses were formulated to measure clinical and surrogate endpoints. Objectives and Hypotheses we posit that conscious pairing adequately pleasant stimuli with tinnitus perception results in correction of the Loudness Misperception. Given anatomical and functional targeting, we propose active HD-tDCS on the left dorsolateral PreFrontal Cortex improves distorted perception in tinnitus. The dose-response relationship between HD-tDCS specificity and the loudness perception is also explored. Method We conducted a double-blind, randomized crossover pilot study with six recruited tinnitus patients. Accrued data was utilized to design a well-controlled adaptive seamless Bayesian dose-response study. Results Preliminary results of the pilot study showed a significant difference (90% power, 1% of significance level) in the co-variance coefficient between before and during positive emotion induction timepoints for active control intervention. Furthermore, with the power of 90% and significance level of 5%, we estimated the sample size n = 47. We also anticipated optimum interims for adaptive decision-making about efficacy, safety, and single session dose parameters. Conclusions This study proposed a novel model to target tinnitus. In the proposed methodology, during the induction of the functional targeting under HD-tDCS montage and dose-finding process, simultaneously neuromodulation efficacy of the intervention was investigated. The continuous updating of prior knowledge adapts anticipated dose-response and simulated curve with the longitudinal model to define the minimum and maximum effective doses resulting in the superiority effect of the neuromodulation approach. Furthermore, this paper supports a technical report for designing multimodality data-driven investigations in emotion regulation, including EEG-driven neuro markers, Stroop-driven attentional biases, and neuroimaging-driven brain network dynamics.